Hypertensive kidney disease in Brazil between 2011 and 2021 - Murrugarra , Lais Kaori Sato; Luz, Kelly Cristina Suzue Iamaguchi; Sanguino, Gabriel Zanin; Silva , Jéssica Vitória Nunes da; Frez , Flávia Cristina Vieira; Sesnik, Heitor Hortensi; Oliveira , Isabela Tatiane de; Santos , Gabriel Vale dos; Luckner, Ana Clara; Felipin, Larissa Carolina Segantini (Seven Editora, 2023)
Hypertensive kidney disease (HCD) is a progressive kidney injury that has its origin due to long-term poorly controlled arterial hypertension, even with prevention campaigns, hypertension is still an important public health problem. The aim of this study was  to describe the number of deaths caused by hypertensive kidney disease in Brazil from 2011 to 2021. This is a descriptive, exploratory study with a quantitative approach, with data collected through access to the DATASUS health data platform. Within the period analyzed, the total number of deaths was 106,973. In the ten years evaluated, the year with the highest number was 2021, totaling 10,979 deaths due to hypertensive kidney diseases. Regarding gender, there were 1,360 deaths in men and 1,185 deaths in women. In view of the data obtained, it is observed that male and elderly patients (60 to 80 years or older) have a greater susceptibility to the development of comorbidities associated with hypertensive renal crisis. This trend can be explained by the fact that men, in general, tend to show less concern with health and lower adherence to self-care practices when compared to women. DOI:https://doi.org/10.56238/sevened2023.004-007